Sedentary Lifestyle of Older Adults and Its Associated Factors: A Multicentre Cross-Sectional Study During COVID-19 Pandemic in Indonesia - Siti Setiati; Kuntjoro Harimurti; Ika Fitriana; Noto Dwimartutie; Rahmi Istanti; Muhammad Khifzhon Azwar; I Gusti Putu Suka Aryana; Sri Sunarti; Agus Sudarso; Dina Aprillia Ariestine; Lazuardhi Dwipa; Novira Widajanti; et al. (Interna Publishing, 2023)
Background: COVID-19 is here to stay, and humans ought to decide how to adapt. We aimed to describe lifestyle changes during COVID-19 pandemic, and to determine the prevalence and factors associated with sedentary lifestyle among older adults. Methods: We obtained data from community-dwelling older adults aged ≥60 years. We presented the data descriptively and used multivariate analysis to assess the association between Physical Activity Scale for the Elderly (PASE) -based sedentary lifestyle and other variables in several tertiary geriatric centres. Results: Among 601 participants, 21.1% had sedentary lifestyle. Ethnic groups with the highest prevalence of sedentary lifestyle were Minang, Balinese, and Sundanese. Changes related to food intake, body weight, and physical activity were seen in a small proportion of older adults. Sun exposure habit was described. Sedentary lifestyle was associated with less consumption of food (OR 2.59, 95% CI 1.07-6.30), weight loss (OR 3.00, 95% CI 1.64-5.48), and higher intensity of snacking (OR 0.45, 95% CI 0.20-0.99). Conclusion: During COVID-19 pandemic, one out of five older adults had sedentary lifestyle, which was positively associated with less consumption of food and weight loss, and negatively associated with higher intensity of snacking. The prevalence of sedentary lifestyle varied across ethnic groups. Adequate and appropriate food intake may be crucial to keep older adults active, preventing them from entering vicious cycle of malnutrition, sarcopenia, and frailty.